Variations in gene expression among different types of human skeletal muscle - Kang, P. B.; Kho, A. T.; Sanoudou, D.; Haslett, J. N.; Dow, C. P.; Han, M.; Blasko, J. M.; Lidov, H. G.; Beggs, A. H.; Kunkel, L. M. (Muscle NerveMuscle NerveMuscle Nerve, 2005)
There is a consistent variation in the response of different skeletal muscle groups to mutations in genes known to cause muscular dystrophy, yet these muscles appear histologically similar. To better understand these phenotypic differences, we analyzed gene expression patterns in control muscle specimens obtained from four sites at autopsy: deltoid, quadriceps, gastrocnemius, and tibialis anterior (TA). A total of 35 muscle samples from nine individuals (four pediatric and five geriatric) were studied. Factors potentially influencing gene expression in the different samples included individuality, age, muscle type, gender, cause of death, postmortem interval, and ethnicity. The first three factors, in decreasing order, were found to have a significant impact on the stratification of muscle specimens. A novel analytic method, using a second round of normalization, was used to elicit differences between muscle types. This approach may be extended to a broader survey, potentially elucidating a molecular classification of the skeletal muscles.
Keywords: *Gene Expression; Adolescent; Adult; Age Factors; Aged; Aged, 80 and over; Aging/*genetics; Cadaver; Child; Child, Preschool; Discoidin Domain Receptors; Electrophoresis; Female; Humans; Infant; Infant, Newborn; Male; Muscle Fibers, Skeletal/cytology/metabolism; Muscle, Skeletal/cytology/*physiology; Phenotype; Receptor Protein-Tyrosine Kinases/genetics/metabolism; Receptors, Mitogen/genetics/metabolism; RNA/*genetics; Sex Factors; spectrophotometry